2012
DOI: 10.1128/jvi.01689-12
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Alternatively Activated Macrophages Enhances Pathogenesis during Severe Acute Respiratory Syndrome Coronavirus Infection

Abstract: e Infection with severe acute respiratory syndrome coronavirus (SARS-CoV) causes acute lung injury (ALI) that often leads to severe lung disease. A mouse model of acute SARS-CoV infection has been helpful in understanding the host response to infection; however, there are still unanswered questions concerning SARS-CoV pathogenesis. We have shown that STAT1 plays an important role in the severity of SARS-CoV pathogenesis and that it is independent of the role of STAT1 in interferon signaling. Mice lacking STAT1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
92
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(97 citation statements)
references
References 78 publications
(104 reference statements)
4
92
0
1
Order By: Relevance
“…In severe acute respiratory syndrome (SARS)-Cov infection, STAT dependent pathway of macrophage polarization insulates the host from development of chronic fibrotic lung disease. M2 macrophages are critical for this process (Page et al, 2012). In addition, mixed M1 and M2 macrophages are associated with severe respiratory syncytial virus (RSV) induced bronchiolitis (Shirey et al, 2010).…”
Section: Infection By Various Pathogensmentioning
confidence: 99%
“…In severe acute respiratory syndrome (SARS)-Cov infection, STAT dependent pathway of macrophage polarization insulates the host from development of chronic fibrotic lung disease. M2 macrophages are critical for this process (Page et al, 2012). In addition, mixed M1 and M2 macrophages are associated with severe respiratory syncytial virus (RSV) induced bronchiolitis (Shirey et al, 2010).…”
Section: Infection By Various Pathogensmentioning
confidence: 99%
“…Work in murine macrophages has demonstrated that influenza infection can result in compromised pathogen clearance, acute inflammation and cell recruitment 31. Infection with the severe acute respiratory syndrome (SARS) coronavirus, the causal agent of SARS, results in a significant accumulation of enlarged M2 macrophages in the lung 32. Spike (S) protein, a major structural component of SARS, induces the conversion of B cells into cells that resemble macrophages, when displayed on recombinant baculovirus 33.…”
Section: Macrophage Mediation Of Airway Diseasementioning
confidence: 99%
“…Additionally, the concept of Mϕ activation status altering the host immune response has been explored in diseases such as diabetes, cancer, and atherosclerosis, where it has been shown that Mϕ populations are skewed to an M1 “pro‐inflammatory” state in diabetes, an M2 “anti‐inflammatory” state in the case of cancer, and both M1 and M2 populations in various aspects of atherosclerosis . A number of studies have also investigated the role of Mϕ polarization in the context of infections with bacterial, parasitic and viral pathogens . Viral pathogens such as HIV can modulate the status of macrophages to avoid the immune response or facilitate proliferation and dissemination, suggestive of the “evolutionary arms‐race” between host and virus .…”
Section: The Impact Of Macrophage Polarization On Ebov Infectionmentioning
confidence: 99%